Prevention and Suppression of Domestic Violence in the Republic of Serbia - Subošić, Dane; Milenković, Dejan (Magyar Rendészet, 2018)
Deriving from the commitments agreed and accepted by the ratification of the convention on preventing and combating violence against women and domestic violence, the National Assembly of the Republic of Serbia (RS) passed a law on countering domestic violence. This paper addresses three issues regarding this matter. The first issue examines the state of security in the domain of domestic violence in the RS. The second issue examines the countering of domestic violence in the Republic of Serbia with special emphasis on the period of 01.06.2017 onwards, since that date is being recognized as the date when this law came into effect. The third issue examines the problems and difficulties of application of this said law in the RS.